An improved method of moments as a more reliable alternative for prediction of average molecular weights of irreversible non-linear polymerizations and reversible polycondensations - Dias, Rolando (2008)
An improved method of moments as a more reliable alternative for prediction of average molecular weights of irreversible non-linear polymerizations and reversible polycondensations